(untitled) (Modern education and development, 2025)
В статье рассматрив1ается история возникновения и развития тхэквондо ITF, его основные особенности и значение. Описаны техника выполнения, философские принципы, а также роль тхэквондо в физическом и моральном воспитании человека. Особое внимание уделено формальным комплексам движений (туль) и соревновательным дисциплинам. Тхэквондо ITF позиционируется как не только боевое искусство, но и средство самосовершенствования и гармонии. The article examines the history of the origin and development of ITF Taekwondo, its main features, and significance. The techniques, philosophical principles, and the role of Taekwondo in physical and moral development are described. Special attention is given to the formal patterns of movements (tul) and competitive disciplines. ITF Taekwondo is presented not only as a martial art but also as a means of self-improvement and harmony.